The Difference That Power Makes: Intersectionality and Participatory Democracy - Patricia Hill Collins (Investigaciones Feministas, 2017)
This essay explores how developing more complex analyses of power and politics sheds light on important themes for both intersectionality and participatory democracy. Drawn from intersectional inquiry, Part I, “Hidden in Plain Sight: Hypervisible Power and Invisible Politics,” outlines three focal points of a provisional power analytic: (1) how analyses of intersecting, structural oppressions underpin systems of domination; (2) how a domains-of-power framework provides a set of conceptual tools for analyzing and responding to intersecting power relations; and (3) how a more robust analysis of the collective illuminates the political action of subordinated groups.